2013
DOI: 10.1186/1750-1172-8-185
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Eculizumab on the pathology of malignant atrophic papulosis

Abstract: BackgroundDegos disease is a frequently fatal and incurable occlusive vasculopathy most commonly affecting the skin, gastrointestinal tract and brain. Vascular C5b-9 deposition and a type I interferon (IFN) rich microenvironment are held to be pathogenetically important in the evolution of the vascular changes. We recently discovered the use of eculizumab as a salvage drug in the treatment of near fatal Malignant atrophic papulosis (MAP). The effects of eculizumab on the pathology of MAP are explored.MethodsAr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 20 publications
0
52
0
2
Order By: Relevance
“…The mortality in all patients with the systemic type was 65.3% (34/52), whereas no patient death was observed among the 28 patients with pure cutaneous involvement ( P < 0.05). In patients with extracutaneous involvement ( n = 43, excluding six patients whose information was not available and three patients with cutaneous involvement after systemic manifestations) . Moreover, we found that in patients in the systemic category, the first systemic manifestation occurred at a median of 2.0 years (95% CI, 0–7.8) after disease onset.…”
Section: Discussionmentioning
confidence: 78%
“…The mortality in all patients with the systemic type was 65.3% (34/52), whereas no patient death was observed among the 28 patients with pure cutaneous involvement ( P < 0.05). In patients with extracutaneous involvement ( n = 43, excluding six patients whose information was not available and three patients with cutaneous involvement after systemic manifestations) . Moreover, we found that in patients in the systemic category, the first systemic manifestation occurred at a median of 2.0 years (95% CI, 0–7.8) after disease onset.…”
Section: Discussionmentioning
confidence: 78%
“…The age at disease onset is 36.5 years (range 5-60), not differing between BAP and MAP. 9 Harvell et al 10 examined histological specimens of the lesions according to the duration of their existence. 5,6 Confocal microscopy could detect additionally densified collagen fibres and a decrease in dermal capillaries inside the connective tissue necrosis but presence of capillary hyperplasia in the periphery of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,16 Eculizumab, a monoclonal antibody which binds C5 complement, has led to dramatic responses in a small number of patients, possibly due to antiapoptotic endothelial effects. 4,17,18 Results of recent use of eculizumab in combination with treprostinil, a prostacyclin analog that may enhance endothelial progenitor cells, are also encouraging. 17 Early success with eculizumab supports complement activation as a potential driving mechanism of MAP, although reports of disease progression after initial response to the drug indicate additional factors at work in disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…17 Early success with eculizumab supports complement activation as a potential driving mechanism of MAP, although reports of disease progression after initial response to the drug indicate additional factors at work in disease pathogenesis. 17,18 …”
Section: Discussionmentioning
confidence: 99%